VD_FINDINFO HC / 2009 / 267 vom 29. September 2009 - VD Tribunal cantonal (2009)
BAIL À LOYER, EXPULSION DE LOCATAIRE, DEMEURE DU DÉBITEUR, FRAIS ACCESSOIRES, RÉSILIATION IMMÉDIATE | 257d al. 1 CO, 257d al. 2 CO, 257d CO, 457 al. 1 CPC, 23 LPEBL, 29 LPEBL